(untitled) (International Journal of Built Environment and Sustainability, 2017)
Rivers, lakes, beaches or other public water bodies have substantial and precious environmental values, and if properly managed, they can be a tremendous element towards a sustainable city. Within the context of urban planning and environmental sustainability, the harmonious balance between built and natural environment could not be avoided. The riverfront development concepts attempt to accomplish this balance by developing the necessary built environment while keeping the natural environment intact and provides ecological service. Since the concept of riverfront development is new to Indonesia or to most cities in Indonesia, it would be a good initiative to promote this concept. The riverfront development concept would bring the positive multiplier effects to urban development and ultimately to the well-being of urban citizens. This paper attempts to address the possibilities of riverfront development concept for its existence from the viewpoint of urban planning and environmental sustainability. This thought is based on personal lookout as well as relevant references. The study was carried out by observing some examples of waterfront development in some cities. Assessment on the regulations of riverfront related development was also undertaken. The study found that present approach on rivers or lakes or other public water bodies as the backyard of the development has brought to various environmental degradation. The riverfront concept is expected to reverse the situation for its numerous social, economic and environmental advantages. We suggest that this concept must be implemented elsewhere in Indonesia due to foreseeable returns towards sustainable urban development and sustainable cities.